2018
DOI: 10.1002/jsfa.9082
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds can delay the oxidation of polyunsaturated fatty acids and the growth of Listeria monocytogenes: structure‐activity relationships

Abstract: The physico-chemical properties of the compounds influenced both activities but not in the same way. The chemical environment of the phenolic group and the presence of delocalization structures are the most important parameters for antioxidant activity, whereas the partition coefficient, logP, is one of the most important factors involved in antibacterial activity. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…It is interesting to investigate the structure-activity relationships for phenylethanoid glycosides 1-4, which have similar structures, and the main differences are the substituents at C-3 (R1), C-4 (R2) and C-4 0 (R3). It is inferred that the antioxidant activity of phenolics increases when there are free hydroxy groups in the molecule, which is consistent with the reported results [33]. Of the six flavonoids analysed (5-10), only luteolin (5) displayed strong antioxidant activities.…”
Section: Plos Onesupporting
confidence: 91%
“…It is interesting to investigate the structure-activity relationships for phenylethanoid glycosides 1-4, which have similar structures, and the main differences are the substituents at C-3 (R1), C-4 (R2) and C-4 0 (R3). It is inferred that the antioxidant activity of phenolics increases when there are free hydroxy groups in the molecule, which is consistent with the reported results [33]. Of the six flavonoids analysed (5-10), only luteolin (5) displayed strong antioxidant activities.…”
Section: Plos Onesupporting
confidence: 91%
“…However, over 57% of color removal was achieved after a retention period of 35 h. The impeded decolorization process observed earlier at this initial concentration (2,600 ADMI) could be due to the predominant complex aromatic ring structure of the recalcitrant contaminants (such as colorants) which are not easily broken by the microbes' metabolic and enzymatic activities (Hameed and Ismail, 2018). In addition, the presence of other toxic compounds (such as sulphonic groups) exerts an inhibitory effect on the extracellular activities of the microbes (Luo et al, 2014;Pernin et al, 2018). Thus, these compounds antagonize the overall bio-decolorization processes (Pernin et al, 2018).…”
Section: Effect Of Initial Concentration At Varied Treatment Time Witmentioning
confidence: 88%
“…This adds to the value of its antimicrobial activity. Quercetin affects the prokaryotic and eukaryotic cells by different modes of action and it is reported that antibacterial activity of quercetin is mediated by the inhibition of nucleic acid synthesis (Cushnie and Lamb 2005;Pernin et al 2018). The flavonoids including quercetin are known to exert their action by proton pump inhibition (PPI).…”
Section: Resultsmentioning
confidence: 99%